Simulasi Disturbance Observer pada Sistem Kendali Aliran Cairan Berbasis Mikrokontroler - Irawan Saputra, Dede; Lukman Hakim, Dadang (EPSILON: Journal of Electrical Engineering and Information Technology, 2024)
This research discusses the design and implementation of a PID controller-based liquid flow control system equipped with a Disturbance Observer (DOB). The system is designed to compensate for the influence of external disturbances that can interfere with control performance. The design process starts with modeling the system dynamics using mathematical equations, followed by designing a PID controller to regulate the flow according to the desired setpoint. The DOB is designed by utilizing the inverse model of the system to estimate the disturbances that occur and compensate for their effects on the control signals in real-time. Simulations were conducted to compare the performance of the system with and without DOB in the face of disturbances. The results show that the system with DOB has better performance, with more stable response, faster recovery time, and smaller steady-state error than the system without DOB. This confirms the effectiveness of DOB in improving the robustness of the control system against external disturbances.